The Development of German Language Learning Mobile Application for Beginners - KOK, QIAN WEI; OTHMAN, MUHAMMAD FAKRI (Applied Information Technology And Computer Science, 2023)
German is one of the international languages that is being encouraged to learn by people all around the world. However, most of the existing German learning applications found are lacking some important features such as German grammar, quizzes, and the function to verify the learners’ pronunciation. Thus, Learn German From Scratch mobile learning application is developed on the Android mobile platform to overcome these problems by integrating the features and adopting the Speech Recognition technology. The information is obtained from the lecture note of the German international language course of UTHM. Multimedia Mobile Content Development methodology is used in developing the application. User acceptance testing has been conducted involving 30 target users and gained a positive result as more than 53% of them are highly satisfied with the developed application. In conclusion, the application has a high user acceptance level and it is suitable to be used as a reference for the student in German language class at UTHM.